Biologia de nidificação de Euglossa cordata (Apidae: Euglossini) em áreas abertas no Extremo Sul Baiano - Silva de Souza Filho, Flávio; Costa Prates, Matheus; da Costa Pina, Welber (Scientia Plena, 2024)
The genus Euglossa comprises a group of approximately 110 cataloged bee species found throughout the Neotropical region. Among these species, Euglossa cordata (Linnaeus, 1758) has a wide distribution in different environments. This research aimed to analyze aspects of the nesting biology of E. cordata in open areas near Atlantic Forest fragments in the Extreme South of Bahia, Brazil. Collections were carried out using PET bottle traps, a methodology commonly employed for capturing Meliponini but adapted for the first time in this study, presenting a low cost and good applicability for studies on Euglossa bees. Ten traps were randomly distributed in open environments at the Federal Institute of Bahia. Three nests of E. cordata were found, with a total of thirteen brood cells and six female emergences in traps 2 and 3. In all nests, the cells were constructed in a circular manner and arranged close to each other. The cells were built with resin and had a scalene trapezoid shape with variations in diameter and length. Studies on bees of the Euglossini tribe, popularly known as orchid bees, often focus on males collected using odor baits. Conversely, studies on females and nesting biology are scarce. Thus, methodologies that facilitate the capture of females and Euglossini nests are extremely relevant for enhancing our understanding of the group.